BALANOCARPOL AND AMPELOPSIN H, TWO OLIGORESVERATROLS FROM STEM BARK OF Hopea odorata (DIPTEROCARPACEAE) - Sri Atun; Nurfina Aznam; Retno Arianingrum; Masatake Niwa (Indonesian Journal of Chemistry, 2006)
Two oligoresveratrol, namely balanocarpol (2) and ampelopsin H (3) had been isolated from the steam bark of Hopea odorata (Dipterocarpaceae). The structures of these compounds were elucidated based on physical and spectroscopic data (MS, 1H and 13C NMR 1D and 2D). The activity of these compounds was evaluated against the 2-deoxyribose degradation induced by the hydroxyl radical generated via a Fenton-type reaction. The result showed that activity each compounds as radical hydroxyl scavenger of balanocarpol, and ampelopsin H with an IC50 1802.3 and 4840.0 μg/mL, respectively. Each compound showed low activity. Vitamin C (IC50 83.9 μg/mL) and butylated hydroxyl toluene (1328.0 μg/mL) were used as positif controls. These results suggest that oligoresveratrols from stem bark of H. odorata may be useful as potential sources of natural antioxidants.